Ocular Manifestations in People Living with HIV/AIDS (PLWHA) at the Kerti Praja Foundation, Denpasar, Bali - Triningrat, A A Mas Putrawati; Handayani, Ariesanti Tri; Juliari, I Gusti Ayu Made; Utari, Ni Made Laksmi; Ratnasari, Ni Luh Made Novi (Universitas Udayana, 2022)
Background and purpose: People living with Human Immunodeficiency Virus - acquired immunodeficiency syndrome (PLWHA) could present various ocular manifestations according to the CD4+ lymphocyte count. This study aims to determine the socio-demographic characteristics and ocular manifestations of PLWHA. Methods: This study is an observational study with a cross-sectional design and consecutive sampling, involving a total of 118 samples, conducted in August 2021 at Kerti Praja Foundation Denpasar. Data were collected through history taking and ocular examinations, which included the variables of gender, age, occupation, residence, working status, level of education, duration of ARV treatment, treatment compliance, visual acuity, anterior segment manifestation, posterior segment manifestation, and CD4 T-cell count. Data analysis was performed with a statistical software. Results: A total of 118 samples were involved in this study, with 53 respondents (44.9%) experienced ocular manifestations and 55.1% did not experience ocular manifestations. The most frequent ocular manifestation identified was dry eye (68.5% found in right eye and 54.9% found in left eye), while only 2 patients have posterior-segment manifestation. Conclusion: The most common ocular manifestation in HIV-infected people on anti-retroviral therapy was dry eye. Screening for dry eye is recommended in PLWHA.